(untitled) (CIPEEX, 2025)
The Augustus School is a private institution providing kindergarten and elementary education, catering to students from Kindergarten 2 to the 5th grade of elementary school. The growing demand for technological solutions in the education sector led the stakeholders of Augustus School to identify the need for a management system that integrates academic and financial functionalities, focusing on administrative agility and efficiency in document generation. The objective of this project is to develop a system that meets these needs by offering an integrated environment for academic control of students, subjects, and teachers. Additionally, it provides advanced financial functionalities, such as payment control and financial reports.